2012
DOI: 10.1021/bm2015812
|View full text |Cite
|
Sign up to set email alerts
|

Early Stiffening and Softening of Collagen: Interplay of Deformation Mechanisms in Biopolymer Networks

Abstract: Collagen networks, the main structural/mechanical elements in biological tissues, increasingly serve as biomimetic scaffolds for cell behavioral studies, assays, and tissue engineering, and yet their full spectrum of nonlinear behavior remains unclear. Here, with self-assembled type-I collagen as model, we use metrics beyond those in standard single-harmonic analysis of rheological measurements to reveal strain-softening and strain-stiffening of collagen networks both in instantaneous responses and at steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 48 publications
(88 reference statements)
9
64
0
Order By: Relevance
“…A more elaborative way to interpret kinetics of gelation and to elucidate the impact of crosslinking on the mechanical properties of networks is to convey the phase angle as a function of time. [ 33 ] The storage (G ′ ) and loss (G ′ ′ ) moduli are related by tan( δ ) = G ′ ′ / G ′ , where δ is the phase angle and tan( δ ) is the loss (damping) factor. Gelation takes place if δ falls below 90 ° , or G ′ ′ / G ′ < 1.…”
Section: Bulk Rheological Analyses Of the Cross-linked Supramolecularmentioning
confidence: 99%
“…A more elaborative way to interpret kinetics of gelation and to elucidate the impact of crosslinking on the mechanical properties of networks is to convey the phase angle as a function of time. [ 33 ] The storage (G ′ ) and loss (G ′ ′ ) moduli are related by tan( δ ) = G ′ ′ / G ′ , where δ is the phase angle and tan( δ ) is the loss (damping) factor. Gelation takes place if δ falls below 90 ° , or G ′ ′ / G ′ < 1.…”
Section: Bulk Rheological Analyses Of the Cross-linked Supramolecularmentioning
confidence: 99%
“…These gels undergo stress relaxation in response to an applied strain: the initial stress resisting an applied strain decreases over time due to reorganization processes that relax the stresses in the matrix. In the case of collagen gels typically used for in vitro studies, viscoelasticity and stress relaxation likely arise from unbinding of the weak interactions, such as hydrophobic and electrostatic forces, which hold the fibers in a network (19)(20)(21). Interestingly, recent studies have found that viscoelasticity in synthetic hydrogels used as cell culture substrates can influence cell behaviors such as spreading, proliferation, and differentiation (22-25).…”
mentioning
confidence: 99%
“…More specifically, at small strains (less than 10%) the gels soften slightly with an increase in strain, followed by a rapid increase in the elastic modulus with strain. Both strain-softening [31] and strain-stiffening [31,34] responses have been previously reported in collagen networks, although the microstructural origins are still under intense investigations. Importantly, these observations imply that collagen gels are nonlinear elastic materials [35], implying that its mechanical property can be altered by the amount of deformations in the gels.…”
Section: Mechanical Characterization Of Collagen Matricesmentioning
confidence: 99%